DAMPAK PPN 12%, PERTUMBUHAN PENJUALAN, DAN STRUKTUR ASET TERHADAP EFEKTIVITAS MODAL KERJA DENGAN STRATEGI KEUANGAN SEBAGAI PEMODERASI: (STUDI PADA INDUSTRI MAKANAN DAN MINUMAN DI BEI) - Stevanus Willyam Adi Setiawan; Mohammad Hatta Fahamsyah (Politeknik Negeri Ambon, 2026)
Introduction: This study examines the effect of a 12% Value Added Tax (VAT) policy, sales growth, and asset structure on the effectiveness of working capital, with financial strategy as a moderating variable, in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX). The aim of this study is to explore how changes in fiscal policy and internal company factors interact in influencing financial efficiency and liquidity.Methods: Using a quantitative panel data approach, this study employs Moderated Regression Analysis (MRA) to test the causal relationship between the independent variables (VAT policy, sales growth, and asset structure) and the dependent variable (working capital effectiveness), as well as the moderating role of financial strategy. MRA allows the inclusion of interaction terms to identify how the moderating variable strengthens or weakens the main relationships.Results: Asset structure has a significant positive impact on working capital effectiveness, whereas the 12% VAT policy and sales growth do not. Furthermore, financial strategy significantly moderates the relationship between asset structure and working capital effectiveness, thereby strengthening the positive influence between them.Conclusion and suggestion: Companies with a solid financial strategy can improve their liquidity efficiency and mitigate the financial pressures posed by the VAT increase. These findings demonstrate the importance of sound financial management and an adaptive strategy for maintaining operational stability amidst a changing fiscal environment. Keywords: 12% VAT Policy, Asset Structure, Capital Effectiveness, Financial, MRA, Sales Growth, Strategy, Working